2012
DOI: 10.1083/jcb.201201144
|View full text |Cite
|
Sign up to set email alerts
|

Critical role for the kinesin KIF3A in the HIV life cycle in primary human macrophages

Abstract: KIF3A is important for the intracellular transport of HIV-containing compartments and HIV release from infected macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 43 publications
0
46
0
1
Order By: Relevance
“…In this present study, we found that eATP represents a microenvironmental stimulus capable of inducing rapid discharge of VCCassociated virions from infected macrophages. Given that at least one-third of VCC have been reported to be connected to the plasma membrane (11,21), the gross morphological changes associated with eATP stimulation, resulting in cell contraction and membrane blebbing, could lead to an increased tension of the plasma membrane. VCC may then open up, bringing important amounts of membranes to the plasma membrane and thereby reducing the tension along with the release of the VCC content in the extracellular milieu.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this present study, we found that eATP represents a microenvironmental stimulus capable of inducing rapid discharge of VCCassociated virions from infected macrophages. Given that at least one-third of VCC have been reported to be connected to the plasma membrane (11,21), the gross morphological changes associated with eATP stimulation, resulting in cell contraction and membrane blebbing, could lead to an increased tension of the plasma membrane. VCC may then open up, bringing important amounts of membranes to the plasma membrane and thereby reducing the tension along with the release of the VCC content in the extracellular milieu.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, VCC are believed to represent intracellular sequestration of plasma membrane areas rich in a subset of tetraspanins (12). Likely because of their origin, VCC can be transiently (11) connected to the extracellular medium through microchannels or conduits (21,22). Of interest, VCC-like compartments accessible by the extracellular medium preexist in uninfected macrophages and express similar markers, including CD9, CD81, CD63 (23), and, identified more recently, CD36 (24).…”
Section: Hiv Type 1 (Hiv-1) Infects Cd4mentioning
confidence: 99%
“…These compartments are termed intracellular PM-connected compartments (IPMCs) (24). Previous studies have also suggested the involvement of host cellular components, such as kinesins, in formation and/or dynamics of VCCs or IPMCs (27,28).…”
mentioning
confidence: 99%
“…With the advent of superresolution microscopy, it became possible to examine viral processes unhindered by the diffraction limit. The initial studies using PALM (photoactivated localization microscopy) documented Gag puncta at the plasma membrane (44), while more-recent analyses focused on HIV-1 entry and trafficking (45,46) and HIV-1 Gag assembly (47)(48)(49)(50)(51) and revealed the localization of the restriction factor tetherin relative to Gag and Env (52). Finally, a very recent study, which provided subdiffraction mapping of Gag and Env at the plasma membrane (53), along with elegant correlative electron/fluorescence microscopy (54,55), addresses the specificity of Env recruitment and its incorporation into budding particles.…”
mentioning
confidence: 99%